Multilingualization on the Current Japanese Prefectural Government Web Pages: The Support Status of Easy Japanese for Foreigners - Suzuki, Yoshitaka; Ooe, Masato; Li, Caihuan; Kusrini, Dewi; Yakin, Husnul (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2024)
The multilingualization of Web sites with high quality is essential due to the number of foreigners residing in Japan increasing, web pages need to be translated to obtain information. In this study, we conducted a survey to clarify the current status of language descriptions, including easy Japanese, on prefectural government Web pages. The survey method was to record the language tabs of each prefectural government's Web page and to investigate the number of prefectures that had a tab for easy Japanese in their language tabs. There were 47 Prefectural Government Web Pages in Japan observed based on the availability of language options. As a result, we found that 6 Prefectural Government Web Pages had easy Japanese pages. The six web pages were Tochigi Prefecture, Tokyo Metropolitan Government, Yamanashi Prefecture, Hyogo Prefecture, Fukuoka Prefecture, Kagoshima Prefecture. It found that the notation of easy Japanese was different in each prefecture. The results suggest that the easy Japanese web pages are useful not only for children and non-native speakers of Japanese but also for people with disabilities. In the future, it is important to examine whether easy Japanese really functions as easy Japanese and makes it easier to obtain information.